2023
DOI: 10.3390/biomedicines11102760
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Associated with Disability Progression and Clinical Activity in Multiple Sclerosis Patients Treated with Glatiramer Acetate

Ignacio Casanova,
María I. Domínguez-Mozo,
Laura De Torres
et al.

Abstract: MicroRNAs (miRNAs) are promising biomarkers in multiple sclerosis (MS). This study aims to investigate the association between a preselected list of miRNAs in serum with therapeutic response to Glatiramer Acetate (GA) and with the clinical evolution of a cohort of relapsing–remitting MS (RRMS) patients. We conducted a longitudinal study for 5 years, with cut-off points at 2 and 5 years, including 26 RRMS patients treated with GA for at least 6 months. A total of 6 miRNAs from a previous study (miR-9.5p, miR-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Different authors investigated the link between miRNA expression and EDSS in serum. Using a backstep multivariate regression analysis, Casanova et al identified hsa-miR-9-5p as significantly correlated with EDSS change over 24 months, mirroring the timeframe of our research [ 34 ]. Conversely, unlike our approach, they did not construct a multivariate model to derive an optimized score associated with EDSS changes over time.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Different authors investigated the link between miRNA expression and EDSS in serum. Using a backstep multivariate regression analysis, Casanova et al identified hsa-miR-9-5p as significantly correlated with EDSS change over 24 months, mirroring the timeframe of our research [ 34 ]. Conversely, unlike our approach, they did not construct a multivariate model to derive an optimized score associated with EDSS changes over time.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, with the logistic model being indicated as a possible marker of progression in this study, some of the microRNAs identified and correlated with PIRA and EDSS appear to have specific associations with the pathophysiology of multiple sclerosis based on the literature. Some miRNAs have been recently proposed as biomarkers for RRMS in serum [ 34 ] and extracellular vesicles (EVs) [ 35 , 38 , 39 ]. In the present study, we showed that miRNA expression levels were associated with PIRA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In MS patients treated with glatiramer acetate for 2 years, serum miR-138-5p levels were down-regulated in cases of no evidence of disease activity (NEDA-3), whereas increased levels of miR-126-3p and miR-146a-5p were measured if confirmed disability progression (CDP) developed [167]. Circulating miR-29b-5p and miR-185-5p can be applied as biomarkers of treatment response to IFN-β [168,169].…”
Section: Neuro-immunology and Mirnas 61 Multiple Sclerosismentioning
confidence: 99%